2010
DOI: 10.13073/0015-7473-60.3.249
|View full text |Cite
|
Sign up to set email alerts
|

Quality Measurement in the Wood Products Supply Chain

Abstract: The purpose of this research is to learn about quality measurement practices in a wood products supply chain. According to the Supply Chain Management paradigm, companies no longer compete as individual entities, but as part of complex networks of suppliers and customers, linked together by flows of materials and information.Evidence suggests that a high degree of integration between supply chain members is essential to achieve superior market and financial performance. This study investigates the potential be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 102 publications
(238 reference statements)
0
3
0
Order By: Relevance
“…The quality in the supply chain can be expressed as conformance to mutually agreed-upon requirements among the partner firms with the aim of improving the performance of transactions in the chain (Lai et al , 2005). In fact, many studies on various industries like construction (Kanji and Wong, 1998; Wong and Fung, 1999; Benerji et al , 2005), healthcare (Dean and Terziovski, 2001; Lagrosen and Lagrosen, 2007; Tutuncu and Kucukusta, 2008) and wood (Espinoza et al , 2010) have further reiterated the significance of embedding QM in refining the firm’s SCM for achieving better SCP. The researchers have emphasized on comparing QM practices of manufacturing and service organizations for achieving enhanced SCP (Beaumont et al , 1997; Woon, 2000; Sohal et al , 2001; Prajogo, 2005; Sengupta et al , 2006; Cudney and Elrod, 2011; Kumar et al , 2011; Ooi, 2014), limiting the focus on the consideration of QM constructs for manufacturing organizations providing associated services.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The quality in the supply chain can be expressed as conformance to mutually agreed-upon requirements among the partner firms with the aim of improving the performance of transactions in the chain (Lai et al , 2005). In fact, many studies on various industries like construction (Kanji and Wong, 1998; Wong and Fung, 1999; Benerji et al , 2005), healthcare (Dean and Terziovski, 2001; Lagrosen and Lagrosen, 2007; Tutuncu and Kucukusta, 2008) and wood (Espinoza et al , 2010) have further reiterated the significance of embedding QM in refining the firm’s SCM for achieving better SCP. The researchers have emphasized on comparing QM practices of manufacturing and service organizations for achieving enhanced SCP (Beaumont et al , 1997; Woon, 2000; Sohal et al , 2001; Prajogo, 2005; Sengupta et al , 2006; Cudney and Elrod, 2011; Kumar et al , 2011; Ooi, 2014), limiting the focus on the consideration of QM constructs for manufacturing organizations providing associated services.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On an operational scale, quality measurement systems may represent an important tool for the alignment of activities along the wood supply chain (Espinoza et al, 2010). However, quality management systems tailored for forest harvesting contractors are often limited to generic sector-wide requirements on quality which limit their use (UNECE/FAO, 2008).…”
Section: Performance Alignmentmentioning
confidence: 99%
“…It has been suggested that the more favorable performance of the kitchen cabinet industry sub-segment is due, in part, to the masscustomized, made-to-order, modular products that are manufactured and sold, as well as improvements in operational capabilities and better management of their supply chain (Buehlmann 2004;Buehlmann et al 2010). Because of its importance for business success, research has been conducted on the implementation of supply chain management practices in the wood products industry (Simpson and Wren 1997;Vlosky et al 1998;Buehlmann 2004;D'Amours et al 2004;Espinoza et al 2010a;2010b), while others have explored the improvement of operations management in forest products industries, particularly through the implementation of "just-in-time" and "lean management" practices (Motsenbocker et al 2004;Cumbo et al 2006;Fricke and Buehlmann 2012a). Also, customization as a competitive advantage in the wood products supply chain has been studied by a number of scholars (Kodzi 2006;Kodzi and Gazo 2007;Moreira et al 2007;Walcher et al 2007;Lihra et al 2008).…”
Section: Introductionmentioning
confidence: 99%